Kariyer Psikolojik Danışması ve Rehberliği Uygulamaları - Yılmaz, Olcay; Ulaş Kılıç, Özlem; Kırdök, Oğuzhan; Mutlu Çaykuş, Tansu; Kırdök, Oğuzhan; Karacan Özdemir, Nurten; Ayaz, Ahmet; Büyükgöze-Kavas, Ayşenur; Kağnıcı, Dilek Yelda; Karacan Özdemir, Nurten; Özdoğan, Hatice Kübra; Işık, Erkan; et al. (2024)
-